Trimethylamine N-oxide Supplementation Abolishes the Cardioprotective Effects of Voluntary Exercise in Mice Fed a Western Diet - Zhang, Hongqi; Meng, Jian; Yu, Haiyan (Frontiers in Physiology, 2017)
Excessive consumption of western diet (WD) induces obesity, resulting in cardiac dysfunction. Voluntary exercise ameliorates WD-induced obesity, but its effect on cardiac dysfunction remains unclear. Recent evidence suggests that elevated trimethylamine N-oxide (TMAO), a gut microbe-derived metabolite, can impair cardiac function in WD-induced obesity. We hypothesized that cardiac dysfunction in WD-induced obesity would be prevented by voluntary exercise but abolished by TMAO supplementation. Male CD1 mice fed a WD were assigned to sedentary, exercise or exercise with TMAO treatment for 8 weeks. Male CD1 mice fed a normal diet (ND) for 8 weeks were assigned to sedentary (control). Compared with ND-sedentary mice, WD-sedentary mice gained significantly more body weight and displayed metabolic abnormalities at the end of the experiment. Echocardiography showed significantly impaired cardiac systolic and diastolic function in WD-induced obese mice. Voluntary exercise partially attenuated weight gain and metabolic disorders, but completely prevented cardiac dysfunction in WD-induced obese mice. Molecular studies revealed that WD-sedentary mice had elevated plasma TMAO levels, along with increased myocardial inflammation and fibrosis, all of which were inhibited by voluntary exercise. Of note, concomitant administration of TMAO had no effects on body weight and metabolic disorders, but it abolished the beneficial effects of voluntary exercise on cardiac dysfunction, myocardial inflammation and fibrosis in WD-induced obese mice. The results suggest that voluntary exercise prevents cardiac dysfunction in WD-induced obesity by inhibiting myocardial inflammation and fibrosis. Moreover, the cardioprotective effects of voluntary exercise in WD-induced obesity can be abolished by TMAO supplementation, which abrogates voluntary exercise-induced changes in myocardial inflammation and fibrosis.